Businessman household economic resilience with maqashid sharia approach in pandemic Covid-19 - Eni Susanti; Muhammad Adi Adrian; Saifudin Zuhri (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2022)
This study wants to examine the economic resilience of business households with the maqashid sharia approach during the covid-19 pandemic. This research uses the mix-method method. Quantitative methods are used to analyze financial planning on household resilience with the maqashid sharia approach. The qualitative method used to determine the business resilience strategy is interviewing. The results showed that all independent variables affected the household business's economic resilience with the maqashid sharia approach. The results also show that the expenditure is smaller than the income received by making a priority scale. There are other sources of income to cover needs. Most of the respondents did not receive assistance from the government, while those who received government assistance were used to meet their needs. There is no business assistance to survive the pandemic, and respondents also want to avoid taking out loans to develop their businesses. Most of the respondents use maqashid sharia (priority scale) to survive.